The contested place of religion in family law - Wilson, Robin Fretwell (Cambridge : Cambridge University Press, 2018)
Like many beliefs, religious views matter across an individual's life and the life cycle of a family - from birth to marriage, through child-rearing, and, eventually, death. This volume examines clashes over religious liberty within the personal realm of the family. Against swirling religious beliefs, secular values, and legal regulation, this volume offers a forward-looking examination of tensions between religious freedom and the state's protective function. Contributors unpack some of the Court's recent decisions and explain how they set the stage for ongoing disputes. They evaluate religious claims around birth control, circumcision, modesty, religious education, marriage, polygamy, shared parenting, corporal punishment, faith healing, divorce, and the end of life. Authors span legislators, attorneys, academics, journalists, ministers, physicians, child advocates, and representatives of minority faiths. The Contested Place of Religion in Family Law begins an overdue conversation on questions dividing the nation.
Machine generated contents note: Foreword Senator Orrin Hatch; Introduction Robin Fretwell Wilson; Part I. The Foundations and Boundaries of Religious Liberty: The Risky Business of RFRAs after Hobby Lobby Elizabeth Sepper; Religion and the Family in the Wake of Hobby Lobby Michael A. Helfand; Part II. Religious Claims at Birth: Religious Exceptionalism and Religiously Motivated Harm Michele Bratcher Goodwin; Contraceptive Access and Religious Liberty: Can We Afford to Protect Both? Mark L. Rienzi; The Contraceptive-Coverage Cases and the Problem of Politicized Free-Exercise Lawsuits Gregory M. Lipper; The Substantial Burden Question: Secular Tools for Secular Courts Michael A. Helfand; Coming Soon to a Court Near You: Male Circumcision in Religious Families in Europe and the United States Eric Rassbach; Part III. Religious Claims in Childrearing: The Easiest Accommodation: Abandoning Other People's Children to Their Parents' Religious Views James G. Dwyer; Marriage Agreements and Religious Family Life Brian H. Bix; Religious Parents Who Divorce Margaret F. Brinig; Regulating the Relationship between Parents: Moving Beyond Marriage and Custody Law Merle H. Weiner; Bad Faith: When Religious Beliefs Imperil Children Dr. Paul A. Offit; By Faith Alone: When Religious Beliefs and Child Welfare Collide Robin Fretwell Wilson and Shaakirrah Sanders; Part IV. Rethinking Marriage After Obergefell: After Obergefell: Locating the Contemporary State Interest in Marriage Kari E. Hong; Transformational Marriage: How to End the Culture Wars over Same-Sex Marriage Robin B. Kar; Divorcing Marriage and the State Post-Obergefell Robin Fretwell Wilson; Why No Polygamy John Witte, Jr.; Scrutinizing Polygamy Under Religious Freedom Restoration Acts Maura Irene Strassberg; Part V. Religious Claims at End of Life: Religion and Advance Medical Directives: Formulation and Enforcement Implications Richard L. Kaplan; Personal Religious Identity at the End of Life Naomi Cahn and Reverend Amy Ziettlow; Part VI. Shaping the Legal Culture of the Family: Taking Colliding Trains Off a Collision Path: Lessons from the Utah Compromise for Civil Society J. Stuart Adams; Family Law and Civil Rights Movements: Examining the Influence of Courts and Legislatures on Racial and Sexual Orientation Equality Anthony Michael Kreis; Latter-Day Constitutionalism: Sexuality, Gender, and Mormons William N. Eskridge, Jr.; Part VII. International Perspectives: The Future of Marriage in Secular Societies Patrick M. Parkinson; A Tale of Fragmentation and Intertwinement: The Sacred and the Secular Systems for Forming and Dissolving Marriages in Israel Karin Carmit Yefet and Arianne Renan Barzilay; Religious Modesty for Women and Girls: A Comparative Analysis of Legal Protections in France and the United States Asma T. Uddin.
Title from publisher's bibliographic system (viewed on 15 May 2018).
Keywords: Domestic relations -- United States; Freedom of religion -- United States; Religious minorities -- Legal status, laws, etc. -- United States